Significance of the Ukrainian loess-palaeosol sequences for Pleistocene climate reconstructions: rock magnetic, palaeosol and pollen proxies - Hlavatskyi , D. V.; Gerasimenko, N.P.; Bakhmutov, V.G.; Bonchkovskyi, O.S.; Poliachenko, I.B.; Shpyra, V.V.; Mychak, S.V.; Kravchuk, I.V.; Cherkes, S.I. (Geofizicheskiy Zhurnal, 2021)
Variations of rock magnetic parameters in loess-palaeosol sequences, related to climatic and environmental conditions during their formation, are a powerful tool for palaeoclimate reconstruction. Combined enviromagnetic study of loess deposits in Ukraine and its assessment for the palaeoreconstruction purposes are carried out in the framework of the National Research Foundation of Ukraine project 2020.02/0406 ‘Magnetic proxies of palaeoclimatic changes in the loess-palaeosol sequences of Ukraine’. Environmental/climatic reconstructions of the past are fulfilled using a significant number of palaeoindicators: morphology and lithological properties of palaeosols and loesses, their pollen assemblages and a wide range of magnetic characteristics. In this paper, we present a multi-proxy approach to palaeoenvironmental reconstructions, and introduce preliminary results obtained from magnetic susceptibility of loess-palaeosol sequences in the northern (at Vyazivok), central (Stari Kaydaky) and southern (Roksolany) parts of the Ukrainian loess belt. The amplitudes of palaeoclimate change established using magnetic proxies are well correlated with the lithological, palaeopedological and palynological patterns of the sites, and with the global oxygen-isotope scale (MIS). Ongoing studies of the Stari Kaydaky section confirm the correlation of the Upper Zavadivka (S3) soil unit and Lower Zavadivka (S4) soil unit with MIS 9 and MIS 11, respectively (this was proved earlier at the Vyazivok and Roksolany sites). The underlying Lubny (S5) pedocomplex likely corresponds to MIS 13, and the Martonosha (S6) pedocomplex to MIS 15. Palaeomagnetic investigations at Stari Kaydaky have not so far reached the Lower Shyrokyne unit, in which the Matuyama—Brunhes boundary has been detected at Roksolany and Vyazivok. The Upper Shyrokyne (S7S1) palaeosol unit has normal polarity and is preliminarily correlated with MIS 17.